Malaysian gastronomy routes as a tourist destination / Artinah Zainal, Ahmad Nizan Zali and Mohd Nizam Kassim - Zainal, Artinah; Zali, Ahmad Nizan; Kassim, Mohd Nizam (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2010)
Globally, food and tourism are increasingly being combined and the development of gastronomy as a tourism product has become a trend recently. The awareness of the importance of food as a heritage component in tourism has been steadily growing. As competition between tourism destinations in the Asia region increases, Malaysian local food and culture are a valuable source to attract tourists. Malaysian gastronomy has a significant identity, and an important role to play since food is closely related to tourist consumption and experience. The tourists’ quest for authentic tastes and experiences has been a fundamental thrust, and in practice tourism destinations strive to develop their own distinctive and unique identities. This emergent trend can be examined as most of the tourist destinations have made a great effort to promote their local cuisines. In line with this, the Malaysian gastronomy route should be in tandem with the cultural activity highlighted.